2009
DOI: 10.1021/nl901661a
|View full text |Cite
|
Sign up to set email alerts
|

Domains in Ferroelectric Nanodots

Abstract: Almost free-standing single crystal mesoscale and nanoscale dots of ferroelectric BaTiO(3) have been made by direct focused ion beam patterning of bulk single crystal material. The domain structures which appear in these single crystal dots, after cooling through the Curie temperature, were observed to form into quadrants, with each quadrant consisting of fine 90 degrees stripe domains. The reason that these rather complex domain configurations form is uncertain, but we consider and discuss three possibilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
126
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(136 citation statements)
references
References 37 publications
10
126
0
Order By: Relevance
“…In dots of single crystals, significant in-plane depolarizing fields can be present, because of the reduced objects lateral size, and induce flux closure loops. Such strong effect of lateral depolarizing fields has been reported by McGilly et al in BaTiO 3 single crystals dots 13,15 . A favourable formation of quadrants facilitating fluxclosure at the mesoscale has been observed in vacuum 13 , whereas 180°superdomains have been evidenced in air 15 , showing the effect of surface charges and depolarizing fields on the domains architecture.…”
Section: Resultssupporting
confidence: 58%
“…In dots of single crystals, significant in-plane depolarizing fields can be present, because of the reduced objects lateral size, and induce flux closure loops. Such strong effect of lateral depolarizing fields has been reported by McGilly et al in BaTiO 3 single crystals dots 13,15 . A favourable formation of quadrants facilitating fluxclosure at the mesoscale has been observed in vacuum 13 , whereas 180°superdomains have been evidenced in air 15 , showing the effect of surface charges and depolarizing fields on the domains architecture.…”
Section: Resultssupporting
confidence: 58%
“…These inplane superdomains are strain-neutral, like those in the right-hand side of our Figure 1. It was found that fourfold vertex closure domains in this material are unstable, unlike those in BaTiO3 [32,101] or PZT, [13] in agreement with the clock-model predictions of Srolovitz and Scott. [51] When treating in the clock model the domain walls, rather than treating the polarization itself, [52] it is clear that bundle-domain switching, which can be described as correlated motion of defects, [86] so that the ferroelastic switching indeed dominates the polarization switching, in analogy to the Kosterlitz-Thouless dominancy in thin superconducting films..…”
Section: Discussionsupporting
confidence: 83%
“…A rich variety of new closure domain morphologies, such as Landau-Lifshitz stripe domains [11,12], vortex and triclinic domains [13], have been predicted in PbTiO 3 , and BaTiO 3 thin films under open-circuit boundary conditions using density functional theory, effective Hamiltonian and interatomic potential models [14,15]. Tantalising experimental evidence for these closure domains in platlets and dots of BaTiO 3 has been presented in the form of 90 • stripe superdomains bifurcated by 180 • domain walls [16][17][18] and recent direct observation of vortices in PbTiO 3 /SrTiO 3 superlattices [19].…”
Section: Introductionmentioning
confidence: 99%